Mistress vs Maid: Race, Class, Nation and Boundaries between Women in Argentine Fiction since the Mid‐Nineteenth Century. - Dunstan, Inés; Pit, Rebekah (Gender & History, 2018)
This article analyses the historical construction of the ‘maid’ and the ‘mistress’ in Argentine literature from the mid-nineteenth century through to today. Inspired by the surprising continuities, as well as the less dramatic changes, in the portrayal of the mistress-maid relationship, it explores literary representations of this ubiquitous but understudied duo. The article reveals how overlapping constructions of gender, race, class, sexuality and national identity have shaped differential understandings of women’s ‘appropriate’ domestic roles. Situating such ideas in relation to contemporary politics and historical legacies of slavery and violence against indigenous and mixed-race peoples highlights the long shadows cast by institutionalised racism. Writers have frequently associated a privileged Argentine identity with the figure of the white mistress and set her in opposition to the figure of the ‘inferior’ non-white maid, suggesting that the white mistresses should maintain racial and class boundaries to preserve order. While this article also examines works that highlight the oppression of the maid, it finds they too have reiterated features of the dominant discourse. We argue that the fraught place of the mistress and the maid in Argentine literature reveals a larger unease with the place of women, especially subaltern women, in Argentina’s national imagination.